Produção virtual de paródias: o uso da sequência didática digital como objeto de aprendizagem - Amorim, Fábio Pires de (2020)
This work aimed to apply a Digital Didactic Sequence (SDD) as a Learning Object (OA) for the virtual production of parodies. This textual genre was explored through a range of digital resources like the smartphone. Therefore, with technological advances and the growth in the use of digital devices in society, a pedagogical proposal that works with textual production in a different way from the conventional and closer to the digital universe, in which students are involved, was considered opportune. using SDD, which provides a dynamic process that enhances the teaching of the Portuguese language. Thus, based on Digital Literacy, it was intended to detect the extent to which digital technologies can dynamically contribute to the development of the production of these parodies, through writing in a virtual environment. The use of this learning object proves to be relevant in the context of “Digital Natives”, in which today's students are inserted, a concept widely discussed in this work. In order to carry out this investigation with a qualitative approach, of the type of action research, a class of 7th grade of elementary school in the municipal network of Boquim - SE was chosen as the target of this pedagogical intervention. The methodology of this investigation had as its main theorist Thiollent (2011), bringing concepts about action research. Therefore, after an accurate study of the approaches of several authors, it was intended to enrich the concepts that guide this research with regard to the study of multi-tools and digital literacy through the studies of the New London Group, as well as text genres, especially in the Bakhtinian view, according to which, genders assume a social function. It appears, therefore, that the results of this research were satisfactory, considering the productions of the participants who met the proposed objectives, demonstrating the relevance of the learning object in question: SDD. Obviously, this work is not intended to exhaust the approaches in the proposed field of study, but rather to broaden the debate regarding the use of multiliteracies, focusing on digital technologies in the teaching of Portuguese.